THE EFFECT OF OPERATIONAL AUDIT AND INTERNAL CONTROL ON PERFORMANCE - Basannang , Siti Mariani; Darmayanti, Novi; Lestari, Tri (Journal of Economic and Economic Policy, 2024)
This study aims to examine the influence of operational audits and internal control on company performance, focusing on UD. Cipta Karya Abadi in Lamongan Regency. Objective: The research explores both the individual and combined effects of these factors on company performance. Methods: Utilizing a quantitative approach, data was collected through questionnaires distributed to 38 employees selected using the Slovin formula and convenience sampling. The analysis employed multiple linear regression, supported by validity, reliability, and classical assumption tests, with a significance level of 5%. Results: The findings reveal that operational audits and internal control collectively have a significant positive impact on company performance. Individually, operational audits positively and significantly affect company performance, while internal control does not exhibit a significant individual effect. Novelty: This research highlights the critical role of operational audits in driving company performance and underscores the limited individual impact of internal control, suggesting areas for managerial improvement. The study contributes to understanding how specific internal mechanisms enhance operational efficiency and overall organizational outcomes